Resistência à flexão de diferentes sistemas de pinos de fibra de vidro personalizados - Dutra, Mateus José (2021)
The objective of this work was to compare the flexural strength of conventional fiberglass posts relined with composite resin to custom adjustable posts and single-body fiberglass posts milled in CAD-CAM. Thirty specimens (n=10) were made with the following retainers: (1) PCM - prefabricated fiberglass posts (Exact no. 2 - Angelus®, Londrina, PR, Brazil) relined with composite resin; (2) PFF - pins milled in CAD-CAM from a Fibercad wafer (Fibercad - Angelus®, Londrina, PR, Brazil); and (3) PPA -adjustable custom pins (Splendor SAP - Angelus®, Londrina, PR, Brazil). The specimens were submitted to the three-point bending test, in a universal testing machine, with a load cell of 2,000 N, which focused its force on the center of the specimens, at a speed of 0.05 mm /min. Mean resistance values were compared between groups, using the 1-factor Anova and Tukey tests, at a significance level of 95%. The results showed that the PFF group presented a superior flexural resistance to the PPA and PCM groups (p=0.000). The PPA and PCM groups did not show statistical differences between them. In conclusion, the pins milled in CAD-CAM (PFF) are the ones that most resist a flexural force among the three materials tested in the experiment.